Pengukuran Kinerja Keuangan PDAM melalui Rasio Likuiditas dan Profitabilitas - Wati, Ika; Machmud, Mulyana; Hasan, Hamida; Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
Analysis of Liquidity Ratio and Profitability in Measuring Financial Performance at the Regional Public Drinking Water Company Tirta Karajae Kota Parepare. This study aims to determine the financial performance of the Tirta Karajae Regional Public Drinking Water Company in terms of liquidity and profitability ratios. This study used quantitative descriptive method. By using secondary data sourced from financial statements consisting of Balance Sheet and Income Statement. Abstrak ditulis dalam bahasa Inggris. The results showed that: Financial performance based on the Liquidity Ratio at the Current Ratio, Quick Ratio, Cash Ratio, and Cash Turnover Ratio from 2020-2022 is in good condition because the calculation results are above industry standards. Meanwhile, the Inventory to Net Working Capital from 2020-2022 is in poor condition because the calculation results are below industry standards. Financial performance based on the Profitability Ratio on Net Profit Margin (NPM), Return on Investment (ROI), and Return on Equity (ROE) from 2020-2022 is in poor condition because the calculation results are below industry standards.